Correction to: Infliximab associated with faster symptom resolution compared with corticosteroids alone for the management of immune-related enterocolitis. Issue 1 (17th April 2019) - Johnson, Daniel H.; Zobniw, Chrystia M.; Trinh, Van A.; Ma, Junsheng; Bassett Jr, Roland L.; Abdel-Wahab, Noha; Anderson, Jaime; Davis, Jennifer E.; Joseph, Jocelyn; Uemura, Marc; Noman, Ali; Abu-Sbeih, Hamzah; et al.
Abstract : Following publication of the original article [1], the authors reported an error in their listed affiliations.